Restoration and Conservation of Priority Areas of Caatinga’s Semi-Arid Forest Remnants Can Support Connectivity within an Agricultural Landscape - Andrés A. Salazar; Eduardo C. Arellano; Andrés Muñoz-Sáez; Marcelo D. Miranda; Fabiana Oliveira da Silva; Natalia B. Zielonka; Liam P. Crowther; Vinina Silva-Ferreira; Patricia Oliveira-Reboucas; Lynn V. Dicks (Land, 2021)
Land-use and land-cover (LULC) changes are major drivers of biodiversity loss in semi-arid regions, such as the Caatinga biome located in the Northeast of Brazil. We investigated landscape dynamics and fragmentation in an area of the São Francisco Valley in the Brazilian Caatinga biome and measured the effect of these dynamics on ecological, functional and structural connectivity over a 33-year period (1985–2018). We calculated landscape connectivity indices based on graph theory to quantify the effect of further agricultural expansion on ecological connectivity at the landscape scale. We used a multicriteria decision analysis that integrates graph-based connectivity indices at the habitat patch scale, combined with an index of human disturbance to identify patches that, if conserved and restored, preserve the connectivity of the landscape most effectively. In the period studied, agriculture increased at a rate of 2104 ha/year, while native Caatinga vegetation decreased at a rate of 5203 ha/year. Both dense and open Caatinga became more fragmented, with the number of fragments increasing by 85.2% and 28.6%, respectively, whilst the average fragment size decreased by 84.8% and 6.1% for dense and open Caatinga, respectively. If agriculture patches were to expand by a 300 m buffer around each patch, the overall ecological connectivity could be reduced by 6–15%, depending on the species’ (small- to mid-size terrestrial vertebrates) mobility characteristics for which the connectivity indices were calculated. We provided explicit spatial connectivity and fragmentation information for the conservation and restoration of the Caatinga vegetation in the studied area. This information helps with conservation planning in this rapidly changing ecosystem.